PPKn Teachers’ Role in Promoting Integrity to Prevent Bullying at SMK Karya Bakti, Batu Bara - Sri Al Fatia; Syarbaini Saleh (Journal of General Education and Humanities, 2025)
Bullying remains a prevalent issue in many school environments, including vocational institutions, with harmful effects on students’ psychological well-being and social development. While previous studies have explored general bullying prevention strategies, limited attention has been given to how integrity-based character education, led explicitly by Pancasila and Citizenship Education (PPKn) teachers, contributes to this effort. Addressing this gap, the present study aimed to describe the role of PPKn teachers in strengthening integrity character education to prevent bullying at SMK Karya Bhakti, Batubara Regency. This study used a qualitative descriptive approach, with data collected through observation, in-depth interviews, and documentation. The participants consisted of PPKn teachers, homeroom teachers, and selected students who were purposefully chosen based on their involvement in character-building efforts. Data were analyzed using Miles and Huberman’s interactive model, including data reduction, display, and conclusion drawing. The findings revealed that PPKn teachers played a strategic role in shaping students’ integrity, particularly through learning emphasizing honesty, responsibility, and exemplary conduct. Teachers also contributed by fostering an inclusive classroom climate and employing persuasive, educational approaches in addressing bullying behavior. Their involvement extended beyond formal instruction to daily interactions that modeled ethical behavior.